اقتراح نظام تشفير مستند على نظرية الفوضى والمنطق الغامض - ساري حاج حسين (Tishreen University, 2019)
لقد كشفت الأبحاث أن قدرة العقل البشري على معالجة مقادير ضخمة من المعلومات لحظياً إنما يعود إلى التطور والتغير الشديدين في الديناميكية الفوضوية، وهذا، حقيقةً، ما يجعل العقل البشري مختلفاً عن آلة الذكاء الصنعي. ويسود حالياً اعتقاد مفاده أن المنطق الغامض ونظرية الفوضى متصلان بالحجة البشرية ومعالجة المعلومات، كما يُعتقد أيضاً أن البيانات الغامضة والاستنباط المنطقي الغامض مهمان للغاية في المعالجة المعقدة للمعلومات التي تتم داخل العقل البشري؛ وذلك لأنّ تقديم أوصاف رياضية دقيقة لهذه العمليات والنماذج أمرٌ مستحيلٌ في إطار المعرفة العلمية المتاحة للبشر اليوم. نقدم في هذا البحث تطبيقاً على التكامل ما بين نظرية الفوضى والمنطق الغامض يتمثل بنظام تشفير فوضوي غامض. نحاول فيه أن نقدم مقاربة جديدة وواعدة ربما تستند عليها الأبحاث النظرية والاستقصاءات التي تستهدف الذكاء البشري في المستقبل. Researches have revealed that due to the drastically evolving and changing chaotic dynamics the human brain can process massive information instantly. It is actually what makes the brain different from an artificial-intelligence machine. Currently, it is widely believed that both fuzzy logic and chaos theory are related to human reasoning and information processing. It is also believed that to understand the complex information processing within the human brain, fuzzy data and fuzzy logical inference are essential, given that precise mathematical descriptions of such models and processes are clearly out of question within the framework of scientific knowledge available to human beings nowadays. In this paper, a practical example of integrating fuzzy logic and chaos theory, represented by a Fuzzy Chaotic Cryptosystem (FCC), is introduced. An attempt is also being made to provide a new and promising approach that might be adopted by theoretical researches on and investigations about human intelligence in the future.